Pengembangan Media Pembelajaran Berbasis GeoGebra Untuk Meningkatkan Motivasi Belajar dan Representasi Matematis Siswa di SMA Negeri 1 Lembar - Mawarni, Mawarni; Ahmad Muzaki; Ade Kurniawan (Lembaga Pusat Kegiatan Belajar Masyarakat (PKBM) Tunas Harapan, 2024)
This research This research aims to produce a product in the form of valid, practical and effective media from GeoGebra-based learning media in increasing students' learning motivation and mathematical representation at SMA Negeri 1sheet. This type of research is development research with the ADDIE model. The population used in this research was class XI MIPA 3 students, namely 31 students with a total sample of 6 students. Research data was obtained using learning media validation questionnaires, validation of test instruments, teacher and student responses, as well as students' mathematical representation tests in the form of pre-test and post-test questions. Based on the assessment results from media experts and material experts, it shows that the media developed is included in the